Pengukuran Kualitas Hidup Pasien Kanker Payudara di Kota Denpasar Menggunakan Instrumen EQ-5D-5L - Abdillah Mursyid; Restu Nur Hasanah Haris; Dwi Endarti; Chairun Wiedyaningsih; Susi Ari Kristina (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Breast cancer is the second most common cancer in the world and is one of the biggest causes of cancer deaths every year. Measurement of the quality of life in breast cancer patients could improve treatment and become a prognosic factor along with medical parameters for the patients. This study aims to measure the life quality of breast cancer patients and observe how it affects the life quality based on patient characteristics. The study was conducted on 93 breast cancer patients. Data were collected form patients in several breast cancer comunities in Denpasar which were carried outh within 3 months (January – March 2019). This study used a cross sectional design using a snowball sampling technique involving breast cancer patients in several cancer communities in Denpasar. The patient's life quality data was obtained using the EuroQol-5 Dimension-5 Level (EQ-5D-5L) generic instrument and conversion to health utility (utility) used the Indonesian value set. The entire data was analyzed using the independent t-test and multivariate regression. The results showed that pain/discomfort and anxiety/depression were the most dominant problem in breast cancer patients (82,7%). The utility value of breast cancer patients was 0.821±0.123 and the VAS value was 74.41±11.67. There was a significant difference in utility value based on patient characteristics of occupation (p=0.035), symptoms (p=0,003), and cancer stadium (p=0.015). Affected 20.5% of the quality of life of breast cancer patients in Denpasar city.